2010
DOI: 10.1159/000273466
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Surgical Treatment of Patients with Upper versus Lower Urinary Tract Urothelial Carcinoma: Stage-by-Stage Comparison

Abstract: Objectives: It remains controversial whether we can apply similar principles in the management of upper urinary tract urothelial carcinoma (UUT-UC) based on the behavior of bladder urothelial carcinoma (B-UC). We sought to assess whether UUT-UC and B-UC have similar biology and performed a stage-by-stage comparative analysis of outcome between the 2 groups. Methods: A retrospective review was performed on patients who underwent nephroureterectomy for UUT-UC and radical cystectomy for B-UC from 1991 to 2006. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…The highest risk of UUTR has been reported in patients with a positive surgical margin involving the anastomosis of the ureter and the urinary diversion. Since patients with UUTR after RC tend to have a worse outcome than those with initial tumour of the upper urinary tract achieving negative ureteral surgical margins is viewed as paramount [1,2,3], although it was shown that invasive urothelial cancer of the upper urinary tract appears to have similar tumour biology and outcome compared to BC of the lower urinary tract [8]. …”
Section: Discussionmentioning
confidence: 99%
“…The highest risk of UUTR has been reported in patients with a positive surgical margin involving the anastomosis of the ureter and the urinary diversion. Since patients with UUTR after RC tend to have a worse outcome than those with initial tumour of the upper urinary tract achieving negative ureteral surgical margins is viewed as paramount [1,2,3], although it was shown that invasive urothelial cancer of the upper urinary tract appears to have similar tumour biology and outcome compared to BC of the lower urinary tract [8]. …”
Section: Discussionmentioning
confidence: 99%
“…An additional advantage of administering chemotherapy in the preoperative setting is that the patient has better renal function before RNU, thus allowing administration of cisplatin-based therapy. In patients with bladder cancer, neoadjuvant chemotherapy has also been shown to improve survival [22], and it has been postulated that this benefit may be extrapolated to patients with UTUC [19,23]. Investigators have also shown a survival benefit for more extensive lymphadenectomy in patients with UTUC with locally advanced disease [24].…”
Section: Introductionmentioning
confidence: 99%
“…Rink et al found stage-specific different oncologic outcomes between UTUC and UCB following radical surgery, 9 whereas others reported comparable oncologic outcomes. 16 Nevertheless, studies showed that OS from the time of upper tract recurrence after RC was poor, and median OS was 0.8 to 4.6 years with most patients dying of metastatic disease. 2, 3, 17 Favaretto et al previously reported the 5-year CSS of 78% in patients with primary UTUC at our institution, excluding patients with previous or concurrent RC.…”
Section: Discussionmentioning
confidence: 99%